Pengaruh Human Relation dan Lingkungan Kerja terhadap Etos Kerja Dinas Energi dan Sumber Daya Mineral Provinsi Sumatera Barat - Magdalena, Maria; Maharani, Bintang (Lembaga Yasin AlSys, 2025)
Employee work ethic is one of the key factors in improving organizational performance, particularly in the government sector. However, low levels of enthusiasm and work motivation among employees can still be found, which may affect the achievement of organizational goals. This study aims to analyze the influence of human relation and work environment on employee work ethic at the Energy and Mineral Resources Office (Dinas Energi dan Sumber Daya Mineral or ESDM) of West Sumatra Province. A quantitative approach with a survey method was used. The population of the study consisted of all 62 employees of the ESDM Office, and total sampling was applied. The instrument used was a closed-ended questionnaire with a Likert scale, while the data analysis technique was multiple linear regression processed using SPSS software. The results show that the human relation variable has a positive and significant effect on employee work ethic, with a t-value of 3.827, greater than the t-table value of 1.67109, and a significance level of 0.000 < 0.05. Similarly, the work environment variable also has a positive and significant effect, with a t-value of 2.148 > t-table 1.67109 and a significance level of 0.036 < 0.05. These findings indicate that improving the quality of interpersonal relationships among employees and creating a conducive work environment can significantly enhance work ethic. Therefore, both factors should be prioritized in human resource development strategies within government institutions.